Cultivating disruptive subjectivities: Interrupting the new professionalism - Kathryn Herr (Arizona State University, 2015)
This paper explores the everyday enactments of new public management in our professional lives utilizing principles of self-ethnography. Drawing on the reworking of an Action Research class, I explore the possibilities of a contextual analysis of the workplace to make more transparent the enactment of new public management. Little is known regarding how NPM plays out on the ground in local sites and how, in interacting with the culture it creates, professionals locate themselves and their work. I offer a close examination here of our changing context to explore the techniques and forms of power of NPM in the realms of higher education as well as how we might enact a politics of refusal.